Tradisi Grebeg Suro dalam Perspektif Teori Tindakan Max Weber - Nurrohmah, Elina (Studi Budaya Nusantara, 2023)
Indonesia is a multicultural country. One region has a different topography with other regions so that the culture formed in each region is different. Culture is not something that is formed suddenly, but from a learning process which is then passed down from generation to generation. Ponorogo, known as the City of Reog, has a tradition called Grebeg Suro. Grebeg Suro is a tradition of celebrating the Islamic new year, namely 1 Muharram or 1 Suro on the Javanese calendar. This tradition is held in the form of a folk party. The purpose of this research is to analyze the Grebeg Suro tradition through the perspective of Max Weber's theory of action. This research is a type of qualitative research using the interview method to obtain primary sources and literature studies as secondary sources. The informants interviewed were natives of Ponorogo who had witnessed or participated directly in the Grebeg Suro tradition. The literature used is in the form of articles published in journals and book. From the research results obtained, it can be seen that Weber divides social action into four types, including (1) instrumental rational action; (2) value rational action; (3) traditional actions; and (4) affective action. The Grebeg Suro tradition contains three of the four types of social action. First, value rational actions represented by activities based on religious values, such as tadarus or simaan Al- Qur'an, istighosah, praying together, to Buceng Porak. Second, the traditional actions shown by the Bedhol Pusaka ritual and the Larungan Doa at Telaga Ngebel. Finally, the affective action is marked by a feast or salvation event that aims to share sustenance with others.